Convergent invention in space and place: a rhetorical and empirical analysis of Colorado State University's Morgan Library - Weber, Victoria, author; Dunn, Thomas R., advisor; Aoki, Eric, committee member; Lederer, Naomi, committee member (Colorado State University. Libraries, 2014)
This thesis seeks to describe the ways in which contemporary academic library spaces facilitate rhetorical invention. To observe rhetorical invention in a real space, this thesis analyzes spatial practices in Colorado State University's Morgan Library. This thesis argues that Morgan Library is a representative space of convergent invention. The neologism convergent invention is defined as the cross-platform and multi-modal creation of a rhetorical text which accounts for external factors on the creator(s). To describe the functions of the contemporary library, this thesis uses Michel de Certeau's theories of strategies and tactics to articulate usage patterns. Strategies are analyzed through a rhetorical criticism of Morgan Library to show how the library materially articulates its vision of convergent invention. Users' tactics to accept or reject Morgan Library's messages about convergent invention are explicated through the results of survey data and behavior observations. In the conclusion this thesis provides some implications for convergent invention and the future of libraries, both academic and otherwise.
Keywords: Colorado State University; rhetorical invention; mixed methods; Michel de Certeau; media convergence